HUBUNGAN KONSEP DIRI DAN STRATEGI BELAJAR DENGAN PRESTASI BELAJAR MATAKULIAH PENDIDIKAN BERWAWASAN GLOBAL MAHASISWA PRODI PGSD FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS SLAMET RIYADI SURAKARTA TAHUN AKADEMIK 2014/2015 - Alfonsa Maria Sofia Hapsari, Oktiana Handini (Widya Wacana: Jurnal Ilmiah, 2015)
The research aims at knowing the relationship of self concept and teaching strategy tolearning achievement on subject : Pendidikan berwawasan global students of PGSD FKIPUNISRI.The results of research are (1) self concept has positive correlation to students learningachievement, (2) ) learning strategy has positive correlation to students learning achievement, (3)self concept and learning strategy has positive correlation to students learning achievement.